Monoterapia rytuksymabem w pęcherzycy liściastej - Małgorzata Olszewska; Lidia Rudnicka; Marta Kurzeja; Justyna Sicińska; Agnieszka Kardynał (Termedia Publishing House, 2011)
Introduction. Rituximab is a chimeric human-mouse monoclonal antibody,which binds to the CD20 antigen on B and pre-B lymphocytesand causes depletion of CD20+ cells in the mechanism of complement-dependent and independent cytolysis, antibody-dependent cell cytotoxicityand the mechanism of apoptosis. Rituximab is currently registeredfor the treatment of non-Hodgkin's lymphoma, chronic lymphocyticleukaemia and rheumatoid arthritis. Rituximab has alsodemonstrated efficacy in a number of other autoimmune diseases, includingsystemic lupus erythematosus and Sjögren's syndrome. In severeor recalcitrant cases of pemphigus vulgaris and pemphigus foliaceus,rituximab was applied as an adjuvant drug.Objective. To present the efficacy of rituximab monotherapy inpatients with pemphigus foliaceus, who had contraindications to classicimmunosuppression, and a review of the literature.Case reports. We present 2 patients with pemphigus foliaceus, a 66-year old male and a 61-year old female, treated with rituximab inmonotherapy as a first-line treatment. In the first patient serologicalnegativisation and improvement were observed 4 months after therapyinitiation. After 8 months further, significant clinical improvement,with sparse residual lesions, was observed. In the second case similarresults were achieved.Conclusions. In patients with pemphigus foliaceus significant improvementwas observed after rituximab monotherapy. Serological negativisationwas achieved prior to clinical remission. This unusual phenomenonmay be explained by rapid depletion of CD20+ cells andinhibition of antibody production, while in vivo bound pathogenicpemphigus antibodies remained active.